Teste clínico de resistência muscular inspiratória e equação preditiva para indivíduos saudáveis - Munno, Carolina Moraes da Costa (2020)
The assessment of muscle respiratory performance can be performed through respiratory muscle strength and respiratory muscle endurance (RME). Despite the clinical importance of evaluating RME, the variety of tests and equipment cited in the literature, it is still possible to find gaps in relation to predictive equations and reference values for Brazilian users. Regarding RME, there were no studies on reference values and predictive equations for the same population. Justifying, thus, a realization of the studies of this thesis. Study I was performed with the aim of verifying the reliability of the inspiratory muscle endurance (IME) test in healthy individuals. It was a study in the test-retest design, which included 100 healthy individuals, aged 20 to 80 years, of both genders, who were submitted to IME assessment, through an incremental test, using the equipment threshold loading Powerbreathe® K3 (Gaiam Ltd; Southam, Warwickshire, UK). The highest load sustained for at least 15 breaths was considered the sustained maximum inspiratory pressure (SMIP) value. An excellent reliability was found for the SMIP variable, both for the intra-rater analysis (women=0.978/men=0.982) and for the inter-rater analysis (ICC - women=0.913/men=0.993), in addition to presenting a standard error low measurement for both genders. In the Bland-Altman analysis, the average error in the intra-rater analysis was 2.31 and 0.05 cmH2O, in the inter-rater analysis of -0.03 and 0.05 cmH2O for females and males, respectively. It was concluded that the incremental IME test was reproducible for healthy adults and elderly individuals of both genders and there was a need for only one test to assess SMIP. These findings helped in the elaboration of Study II aimed to propose a clinical test to assess IME, to verify the influence of respiratory muscle strength, age, height, body mass and body mass index (BMI) on IME and to promote a predictive equation for IME of healthy individuals. To this end, an observational and multicenter study was performed, which included 204 healthy individuals aged 20 to 80 years, who were submitted to the assessment of respiratory muscle strength, through the measures of maximum inspiratory pressure (MIP) and the assessment of IME, through the incremental test, using a threshold loading device, electronically adjusted. After the evaluations, the volunteers were grouped by gender, where each group was subdivided into six subgroups according to the age group. The RMI test was well accepted and tolerated by the volunteers. After the analysis, it can be seen that there was a positive correlation between SMIP and MIP (r=0.646; p<0.001), height (r=0.302; p<0.001) and body mass (r=0.279; p=0.001) and negative correlation between SMIP and age (r= -0.240; p=0.003). It was observed after the multiple linear regression with Stepwise, a degree of association between SMIP, age and gender (r²=0.2613; p<0.001), generating the adjusted model: SMIP=e4.2357 + (0.3324 x gender) - (0.008 x age), with female = 0 and male = 1. It was concluded that there was an increase in the IME in parallel to the increase in inspiratory strength, height and body mass and the IME decreased with advancing age. The use of external flow resistant equipment with electronic valve, for the evaluation of the IME of healthy individuals, proved to be easily applicable in clinical practice. In addition, the use of the predictive equation can contribute to a better understanding of SMIP and provide a better interpretation of the IME values in healthy individuals.